Evolving role of 2B4/CD244 in T and NK cell responses during virus infection - Waggoner, Stephen N.; Kumar, Vinay (Frontiers in Immunology, 2012)
The signaling lymphocyte activation molecule (SLAM) family receptor, 2B4/CD244, was first implicated in anti-viral immunity by the discovery that mutations of the SLAM-associated protein, SAP/SH2D1A, impaired 2B4-dependent stimulation of T and natural killer (NK) cell anti-viral functions in X-linked lymphoproliferative (XLP) syndrome patients with uncontrolled Epstein-Barr virus (EBV) infections. Engagement of 2B4 has been variably shown to either activate or inhibit lymphocytes which express this receptor. While SAP expression is required for stimulatory functions of 2B4 on lymphocytes, it remains unclear whether inhibitory signals derived from 2B4 can predominate even in the presence of SAP. Regardless, mounting evidence suggests that 2B4 expression by NK and CD8 T cells is altered by virus infection in mice as well as in humans, and 2B4-mediated signaling may be an important determinant of effective immune control of chronic virus infections. In this review, recent findings regarding the expression and function of 2B4 as well as SAP on T and NK cells during virus infection is discussed, with a focus on the role of 2B4-CD48 interactions in crosstalk between innate and adaptive immunity.